The Relationship Of Immediate Breastfeeding On Pain Levels In Post Caesaria Sectio Patients In The Kuta Room Of Sumber Kasih Hospital, Cirebon City - Indra Lestari, Pipit; Nurfajriyani, Ika; Fauziah, Firly (LPPM ITEKES Mahardika, 2024)
Delivery with Sectio Caesaria can cause premature delay in breastfeeding. The pain caused by Sectio Caesaria surgery will affect the mother in providing care for the baby, so that there is a delay in breastfeeding early which has an impact on the smoothness in milk production. The purpose of this study was to determine the relationship between pain level and immediate breastfeeding in postoperative Sectio Caesaria patients in the Kuta Room of Sumber Kasih Hospital in Cirebon. The type of research used is quantitative research with a cross sectional approach.. The sample size was 50 respondents. The research instrument is a questionnaire sheet. The results of the study were analyzed univariately and bivariately. More than half of the respondents had severe pain, with 39 patients (78.0%) and 11 patients (22.0%) having moderate pain. More than half breastfed more than 1 hour after delivery, namely 29 patients (58.0%) and 21 patients (42.0%) who breastfed less than 1 hour after delivery. There is a relationship between the level of pain and immediate breastfeeding in postoperative sectio caesaria patients in the Kuta Room of Sumber Kasih Hospital in Cirebon City in 2022 (p value = 0.000).